Gender and Animals in Elif Şafak’s 10 Minutes 38 Seconds in this Strange World Novel - Hasnul Insani Djohar; Rifa Fajri Adhania (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
This article examines the representation of the 20th-century Turkish patriarchal system in Elif Șafak’s 10 Minutes 38 Seconds in this Strange World (2019) novel. It also evaluates how the novel describes the sufferings and the resistance towards oppression through the portrayal of animals subtly linked to gender issues. The approach used in this research is qualitative and presented in descriptive form. The data is collected through phrases referring to animals supporting or resisting the patriarchal authority. This study was framed by the animal metaphor theory and theory of the patriarchal structures proposed by Sylvia Walby (1990). The result of the study discovered that Elif Șafak uses five animal expressions to represent women's sufferings, powerlessness, and lack of freedom, such as wild animal, ram and lamb, pigeon, duck, and rabbits. Contrary, the superior position of men is represented by the mosquito. On the other hand, the wolf is the only animal metaphor that expresses society's opposition to patriarchal power. Meanwhile, bird and butterfly serve as symbols of freedom. However, this study also discovered that there are six animal metaphors formulated against the system that are also subject to oppression and exploitation, such as cat, deer, blue betta fish, horse, turtle, and spider. All in all, almost all the characters depicted as animals in the novel are victims of the 20th-century Turkish patriarchal system and gender issues covering all six aspects of Walby's theory.